Penerapan Teknologi Budidaya Bawang Merah Bima Brebes sesuai Kondisi Agroekosistem untuk Meningkatkan Pengetahuan Kelompok Tani “Bantang Cama”: Application of Bima Brebes Shallot Cultivation Technology according to Agroecosystem Conditions to Increase Knowledge of the "Bantang Cama" Farmer Group - Liana, Devi; Panjaitan, Fany Juliarti; Taopan, Rizki Adiputra; Astuti, Tri; Purba, Dumaris Priskila; Knaofmone, Elfrida; Ariefin, Muhammad Noor; Adi, Defiyanto Djami; Choirunnisa, Jessyca Putri; Mulu, Marlinda; Jelatu, Silfanus; Rofita, Dewi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Shallots are a horticultural commodity with high economic value because shallots are always used in almost every dish. The importance of knowledge about shallot cultivation technology according to the agroecosystem has yet to be fully distributed at the Bantang Cama Farmers Group in Manggarai Regency. The targets to be achieved from this PKM program are increasing the skills of farmer groups in Waso Village regarding the cultivation of Bima Brebes shallots, as well as the results of adaptation of Bima Brebes shallots through the implementation of cultivation carried out in the highlands. Service activities were carried out in the "Bantang Cama" farmer group in Waso Village, Manggarai, East Nusa Tenggara, with 36 participants. They went through the stages of field observation, literature study, outreach, demonstration, and evaluation. The evaluation was carried out using a pretest and posttest to measure the improvement in the skills of the farmer group and see the results of the Bima Brebes shallots that had been cultivated. The results of the service showed that the skills of the farmer group after participating in the socialization increased from 38.50% to 87.60%. Bima Brebes shallots produced low plant height, number of leaves, and tillers. This shows a mechanism of low adaptability to the agroecosystem, the highlands in Waso Village.